P3.216 Assessing hpv genotype prevalence in infection and disease in young australian women following the introduction of a national vaccination program. (8th July 2017) - Garland, Suzanne; Cornall, AM; Brotherton, JML; Osborne, SL; Wrede, CD; Wark, JD; Saville, M; Pyman, J; Tan, J; Callegari, ET; Gertig, DM; Jayasinghe, Y; et al.
Abstract : Introduction: The National HPV Vaccination Program, utilising the quadrivalent HPV vaccine, was implemented in Australia in 2007. As the first country to introduce this scheme, Australia is ideally placed to identify changes in HPV genoprevalence in a vaccinated population, as well as in cervical intraepithelial neoplasia grade 3 (CIN3) lesions. Methods: The VACCINE (Vaccine Against Cervical Cancer Impact and Effectiveness) study was designed to assess prevalence of vaccine-targeted HPV genotype infections. In sub-study A, sexually active Victorian women aged 18–25 years, recruited through targeted social media advertising on Facebook, were asked to complete an online questionnaire and provide a self-collected vaginal swab for HPV DNA genotyping. The National HPV Vaccination Program Register (NHVPR) was utilised to verify self-reported vaccination status. In sub-study B, causal HPV genotypes in 529 CIN3 cases among vaccine-eligible young women were determined using laser capture microdissection and compared with pre-vaccine era data. Results: In sub-study A, 1095 participants were recruited (18% were virginal so no swab was collected) and 774 (77%) completed all study requirements. Vaccine-targeted HPV genotypes were detected in only 13 samples (1.7%); 11 HPV16 and two HPV6: none were in participants vaccinated prior to sexual debut. In sub-study B, 333 women (62.9%) had a HPV16/18 positive CIN3 detected. The pre-vaccine era population included 98 women aged 18–25, and 115 women aged 26–32, recruited between 2001 and 2005. Compared to the pre-vaccine cohort, the proportion of HPV16/18 positive CIN3 was significantly lower in the post-vaccine 18–25 year old group (71.4% vs 54.9%, p=0.009), but was not significantly different in the 26–32 year old age group (61.7% vs 65.9%, p=0.409). Conclusion: The VACCINE study demonstrates that vaccine-related HPV genotype prevalence is remarkably low amongst vaccine-eligible Victorian women, and also demonstrates a reduction in the proportion of CIN3 caused by vaccine preventable HPV types in younger, vaccine-eligible women. Support: : I Professor Suzanne Garland, have received Grants to my institution from Commonwealth Department of Health for HPV genoprevalance surveillance post vaccination, Merck and GSK (GlaxoSmithKline) to perform phase 3 clinical vaccine trials: Merck to evaluate HPV in RRP post vaccination programme, CSL for HPV in cervical cancer study, and VCA (Victoria Cancer Agency) for a study on effectiveness of public health HPV vaccine study plus a study on associations of early onset cancers. I have received speaking fees from MSD and SPMSD for work performed in my personal time. Merck paid for travel and accommodation to present at HPV Advisory board meetings.